Effect of Perovskite Film Preparation on Performance of Solar Cells - Yaxian Pei; Xiaoping Zou; Xiaolei Qi; Gongqing Teng; Qi Li; Dongdong Guo; Shuangxiong Zeng (Journal of Chemistry)
For the perovskite solar cells (PSCs), the performance of the PSCs has become the focus of the research by improving the crystallization and morphology of the perovskite absorption layer. In this thesis, based on the structure of mesoporous perovskite solar cells (MPSCs), we designed the experiments to improve the photovoltaic performance of the PSCs by improved processing technique, which mainly includes the following two aspects. Before spin-coating PbI2 solution, we control the substrate temperature to modify the crystal quality and morphology of perovskite films. On the other hand, before annealing, we keep PbI2 films for the different drying time at room temperature to optimize films morphology. In our trials, it was found that the substrate temperature is more important in determining the photovoltaic performance than drying time. These results indicate that the crystallization and morphology of perovskite films affect the absorption intensity and obviously influence the short circuit current density of MPSCs. Utilizing films prepared by mentioning two methods, MPSCs with maximum power conversion efficiency of over 4% were fabricated for the active area of 0.5 × 0.5 cm2.